Victorian culture and classical antiquity : art, opera, fiction, and the proclamation of modernity - Goldhill, Simon (Martin classical lectures., 2011)
How did the Victorians engage with the ancient world? Victorian Culture and Classical Antiquity is a brilliant exploration of how the ancient worlds of Greece and Rome influenced Victorian culture. Through Victorian art, opera, and novels, Simon Goldhill examines how sexuality and desire, the politics of culture, and the role of religion in society were considered and debated through the Victorian obsession with antiquity. Looking at Victorian art, Goldhill demonstrates how desire and sexuality, particularly anxieties about male desire, were represented and communicated through classical imagery. Probing into operas of the period, Goldhill addresses ideas of citizenship, nationalism, and cultural politics. And through fiction--specifically nineteenth-century novels about the Roman Empire--he discusses religion and the fierce battles over the church as Christianity began to lose dominance over the progressive stance of Victorian science and investigation. Rediscovering some great forgotten works and reframing some more familiar ones, the book offers extraordinary insights into how the Victorian sense of antiquity and our sense of the Victorians came into being. With a wide range of examples and stories, Victorian Culture and Classical Antiquity demonstrates how interest in the classical past shaped nineteenth-century self-expression, giving antiquity a unique place in Victorian culture.--Provided by publisher.